On the Verge of a Catastrophic Collapse? The Need for a Multi-Ecosystem Approach to Microbiome Studies - Larsen, Olaf F. A.; van de Burgwal, Linda H. M. (Frontiers in Microbiology, 2021)
While the covid-19 pandemic has increased attention for pathogenic microbes crossing the animal-human species barrier, calls to include non-pathogenic interactions in our perspective on public health are also gaining traction in the academic community. Over generations, the diversity of the human gut microbiota is challenged by external perturbations and reduced acquisition of symbiotic species. When such reduced diversity concerns not only the microbial species, but also higher taxonomic and even guild levels, adequate compensation for possible losses may be lacking. Shifts from a high-abundance to a low-abundance state, known as a tipping point, may result in simultaneous shifts in covarying taxa, and ultimately to a catastrophic collapse in which the ecosystem abruptly and possibly irreversibly shifts to an alternative state. Here we argue that co-occurrence patterns within and between microbial communities across human, animal, soil, water and other environmental domains should be studied in light of such critical transitions. Improved mechanistic understanding of factors that shape structure and function is needed to understand whether interventions can sustainably remodel disease-prone microbiota compositions to robust and resilient healthy microbiota. Prerequisites for a rational approach are a better understanding of the microbial interaction network, both within and inter-domain, as well as the identification of early warning signs for a catastrophic collapse, warranting a timely response for intervention. We should not forget that mutualism and pathogenicity are two sides of the same coin. Building upon the planetary health concept, we argue that microbiome research should include system level approaches to conserve ecosystem resilience.